A phase III, multi-centre, double-masked randomised controlled trial of adjunctive intraocular and peri-ocular steroid (triamcinolone acetonide) versus standard treatment in eyes undergoing vitreoretinal surgery for open globe trauma (ASCOT): statistical analysis plan. - Lo,JW; Bunce,C; Charteris,D; Banerjee,P; Phillips,R; Cornelius,VR (Trials, 2016)
BACKGROUND: Open globe ocular trauma complicated by intraocular scarring (proliferative vitreoretinopathy) is a relatively rare, blinding, but potentially treatable condition for which, at present, surgery is often unsatisfactory and visual results frequently poor. To date, no pharmacological adjuncts to surgery have been proven to be effective. The aim of the Adjunctive Steroid Combination in Ocular Trauma (ASCOT) randomised controlled trial is to determine whether adjunctive steroid (triamcinolone acetonide), given at the time of surgery, can improve the outcome of vitreoretinal surgery in patients with open globe ocular trauma. This article presents the statistical analysis plan for the main publication as approved and signed off by the Trial Steering Committee prior to the first data extraction for the Data Monitoring Committee meeting report. METHODS/DESIGN: ASCOT is a pragmatic, multi-centre, parallel-group, double-masked randomised controlled trial. The aim of the study is to recruit from 20-25 centres in the United Kingdom and randomise 300 eyes (from 300 patients) into two treatment arms. Both groups will receive standard surgical treatment and care; the intervention arm will additionally receive a pre-operative steroid combination (triamcinolone acetonide) into the vitreous cavity consisting of 4 mg/0.1 ml and 40 mg/1 ml sub-Tenon's. Participants will be followed for 6 months post-surgery. The primary outcome is the proportion of patients achieving a clinically meaning improvement in visual acuity in the study eye at 6 months after initial surgery, defined as a 10 letter score improvement in the ETDRS (the standard scale to test visual acuity). TRIAL REGISTRATION: ISRCTN30012492 . Registered on 5 September 2014. EudraCT2014-002193-37 . Registered on 5 September 2014.